Hubungan Antara Iklim Komunikasi Organisasi Dengan Kepuasan Kerja (Studi Korelasi Iklim Komunikasi Organisasi Dan Kepuasan Kerja Guru Pegawai Negeri Sipil Di Mtsn Se-Kabupaten Ngawi) - Yustianingrum, Febriana, Budi Santosa, M.Si (2017)
In the school environment is not only the teacher, the main challenge of a principal or as a leader is how to maintain the relationship between the communication climate that is established and teachers job satisfaction in school. Principal should be able to solve the problems that occur related to the workload that has been charged. The purpose of this study is determine whether there is a significant relationship between the organizational communication climate with the job satisfaction of civil servant teachers (PNS) in MTsN District of Ngawi. This study uses two main theories of organizational communication theory and job satisfaction. And the supporting theory is motivation theory. The method used is quantitative correlation analysis. Sampling technique used proportional sampling. By classifying the sample members of each civil servant teacher in MTsN throughout Ngawi District in order to balance the number. Questionnaires were distributed to a sample of 162 civil servant teachers from ten MTsN schools in District of Ngawi. From result of data analysis, finding correlation coefficient value equal to 0,591. It shows significant relationship and positive correlation strong enough between organizational communication climate variable and job satisfaction variable. So that can be interpreted the higher the communication climate of the organization the higher the job satisfaction is formed. Climate in an open organization can encourage employees to express their interests and without fear. So dissatisfaction can be handled in a positive and wise way.